Estudio geológico-geotécnico del túnel de acceso a casa de máquinas del proyecto hidroeléctrico minas- San Francisco. - Jiménez Estrella, Christian Alexander (2016)
The hydroelectric project Minas - San Francisco is located in southern Ecuador. Following the Panamerican Highway (Quito-Cuenca-Machala) is approximately 500 km. of the capital, through the parishes of Pucara and San Rafael de Sharug, the pucará canton (province of Azuay). Hydrologically the project is located in the basin of river Jubones and follow a path parallel thereto. The project falls between 668,870 9'630.956.N coordinates and E. Depending on the feasibility study and final design alternative Minas Hydroelectric Project San Francisco (August 2011) the main components of the hydroelectric works are: 1. A close Jubones in the river with a gravity dam under rolled concrete type in the place called San Francisco, 54 m in height measured from the current level of the river bottom. 2. The closure structure is an important element of control and regulation of the reservoir and solid material deposited in the reservoir, the bottom outlet. 3. Work of socket located on the right bank of river Jubones that connects directly to the input of the sluice chamber and the charge tunnel. 4. To enable the construction of the dam, thus it requires the construction of diversion tunnel. This drive is developed along the left bank of the river Jubones. 5. Tunnel Driving or low pressure develops along the right bank of river Jubones 13.9 km in length and is designed for a flow rate of 65.0 m³ / s. 6. A surge tank, vertical, horizontal circular cross section, total height equal to 68 m at the foot restricted orifice to the profile of the natural terrain in the area of Gramalote. 7. The pressure pipe, which will be built underground and reinforced with a diameter equal to 3.77 m and a total length of 566.4 m. 8. The Powerhouse San Francisco, it located underground or cave in the field of Gramalote. It is positioned at elevation 281.32 m s.n.m. The main floor is located at elevation 291.90 m asl Additionally, there will be a separate transformer cavern to house. The electrical substation will be located abroad, in the same sector Gramalote and connected to the transformers through a pit of cables. 9. The discharge channel for gravity flow or free surface, which will be built underground. The project is located in the middle reaches of the river Jubones geologically rests on the Saraguro Group redefined by Dunkley & Gaibor, 1997, as a sequence of subaerial volcanic rocks, calc-alkaline intermediate to acidic, of late middle Eocene to Miocene early.